ALTERATION AND GOLD MINERALIZATION PANINGKABAN AREAS GUMELAR SUB-DISTRICT, BANYUMAS REGENCY, CENTRAL JAVA PROVINCE - Heru Sigit Purwanto; Herry Riswandi (Techno LPPM, 2015)
The research location is located in Paningkaban area and its surrounding areas that included in the areaof Gumelar Subdistrict, Banyumas Regency, and Central Java Province. The objective of the researchwas to show the presence of any structural geology control on research area that affect the distributionpatterns of quartz vein and gold/ore mineralization.The methodology in this research begins with data collecting process, which this preliminary data is thenbeing compiled to determine the next phase of the study. This study covers the geomorphology,stratigraphy, any structural and alteration mineralization observation. The geomorphology of the studyarea composed of the four original forms: volcanic, structural, karsts and fluvial form. The stratigraphycomposed of seven unclassified litho units and two litodem, namely (from old - young): Halang volcanicbreccias unit, Halang sandstone unit, Kumbang andesite lava unit, Tapak volcanic breccias unit, Tapaksandstones, unit Tapak limestone unit, alluvial deposits, and andesite intrusion.Hydrothermal alterations formed in the research area are carefully grouped into three types of alterationzoning and they are argillic alteration, propylitic alteration, and sub-propylitic alteration. Themineralization then is carefully classified as pyrite (FeS2), chalcopyrite (CuFeS2), galena (Pbs), bornite(Cu5FeS4). The macroscopic analysis of the structure in the study area based on the alignment of allegedtraces of the geological structure in the form of fault, or directions of the fold axis alignment, obtainedthe general alignment directions trending N 305° E (NW - SE), and N 055° E (NE - SW).In the research area, the mineralization process is controlled by geological structure such as fault andjoint. The appearance of the mineralization is abundant and can be found many fulfilling the joint zonemainly shear joint trending Northeast - Southwest and Northwest - Southeast, the direction of jointsharpness measured in the field relatively trending North - South. This study will emphasize on themeasurement and detailed analysis to know more about the gold mineralization process and otherminerals controlled by structures patterns. The structural control analysis can really be a good helpinghand in locating the mineralized areas because basically the activity and geological structure controlprocess are corridor for magma and the its rest compound that brings minerals, so the methods ofmineral ores exploration by structure control can be used in determining ore gold mineralized depositsprecipitate on gold deposits system and other minerals on a different area.Keywords: lithostratigraphy, structure, zone of opening, zone of alteration, mineralization, metalminerals